Rare case of low-grade fibro-myxoid sarcoma presenting as a lateral neck swelling - Nimavat, Sharvil M.; Hirani, Narendra; Khilnani, Ajeet Kumar; Warpe, Bhushan; Malhotra, Khushboo G.; Jain, Nikhil P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Low-grade fibromyxoid sarcoma (LGFMS) is an uncommon malignancy. LGFMS is more likely to affect the trunk and extremities in young adults. However, sporadic cases have been reported in many areas of the head and neck region, including the oral cavity, larynx, and oropharynx. LGFMS typically shows areas of collagenized, myxoid stroma with spindle cell appearance in a rolling pattern. Accurate diagnosis is challenging because it can be mistaken for a simple neoplastic entity of round cells. A few cases of LGFMS which have been reported in the head and neck showing that LGFMS is characterized by local recurrence and metastases. Because of the rarity of the head and neck region, there are no specific treatment guidelines or follow-up. Our study presents LGFMS in a 54-year-old patient in the neck region who underwent surgery and was followed up for one year.